No. 4. Map of North America: Engraved to Illustrate Mitchell's School and Family Geography - Young, J. H. (James Hamilton) (S. Augustus Mitchell, 1839)
This map shows North America and some of the surrounding areas. Each of the countries or regions is shaded using various colors. Major cities and capitals are marked (a text box in the lower left gives an "Explanation."). Bodies of water, locations of some Native American Indian tribes, and geographic features are also marked (with relief shown by hachures and spot heights).